KEEFEKTIFAN EKSTRAK TEMBAKAU PUNTUNG ROKOK LINGTING DAN BERBAGAI JENIS PEREKAT PADA BEBERAPA HARI UNTUK MENGENDALIKAN APHIS CRACCIVORA KOCH PADA TANAMAN KACANG PANJANG (Vigna sinensis L.) - Sutikno, Agus; Salbiah, Desita; Purba, Trikorini (PEST Tropical Journal, 2013)
Aphis craccivora Koch is a major pest in long beans. One of the alternative control can beused to minimize the application of chemical pesticides. One of to control pest of cropcan use tobacco extract. The research was conducted at the Plant Pests Laboratory,Faculty of Agriculture, University of Riau from March 2013 until May 2013. Theexperiment consist of two factors with three treatment and four replicated. The first factoris cigarette butts with a sticker: L1 = Rolled 1g/l of water, L2 = Rolled 1g/l of water andlerak, L3 = Rolled 1g/l of water and cream soap. The second factor is infestation days: H1= First day, H2 = Second day, H3 = Third day. The data is analyzed by using the Analysisof Variance (ANOVA) and Duncanâs New Multiple Range Test (DNMRT) at level 5%.The results showed that the better treatment is extract of tobacco cigarette roll butts 1 g/lof water and cream soap with the first day of the application because capable causingtotal mortality of 85%.Keywords: Aphis craccivora Koch, Long Beans (Vigna sinensis L), TobaccoExtract.